Incidence, clinical characteristics, and outcomes of nosocomial Enterococcus spp. bloodstream infections in a tertiary-care hospital in Beijing, China: a four-year retrospective study - Zhang, Yangyang (Antimicrob Resist Infect Control, 2017)
BACKGROUND: Enterococcus spp. are the common cause of nosocomial bloodstream infections (BSIs) with high morbidity and mortality. The purpose of this study was to characterize the incidence, clinical and microbiological features, and mortality of nosocomial enterococcal BSIs at a large Chinese tertiary-care hospital in Beijing, China. METHODS: A retrospective cohort study on adult patients with nosocomial BSIs due to Enterococcus spp. was performed between January 1, 2012, and December 31, 2015 at the Chinese People’s Liberation Army General Hospital. Patients’ data were gathered by reviewing electronic medical records. RESULTS: A total of 233 episodes of BSI due to Enterococcus spp. occurred among 224 patients during these 4 years. The overall incidence was 3.9 episodes per 10,000 admissions. Enterococcus faecium (E. faecium) was the major pathogen (74%, 95% CI 68–80%), followed by Enterococcus faecalis (E. faecalis) (20%, 95% CI 15–25%). E. faecium showed higher antimicrobial resistance than E. faecalis. The 30-day mortality of nosocomial enterococcal BSI was 24% (95% CI 18–29%). Predictors for mortality included the Acute Physiology and Chronic Health Evaluation II (APACHE II) score, Charlson comorbidity index (CCI), impaired renal function, prior use of immunosuppressive agents, and appropriate empirical antimicrobial treatment. CONCLUSIONS: This study emphasizes that Enterococcus spp. were major pathogens for nosocomial BSIs and associated with high mortality. Appropriate empirical antimicrobial treatment can improve outcomes. Vancomycin is the best choice for patients with E. faecium BSIs. Penicillins, aminoglycosides, fluoroquinolones, and vancomycin can be considered for patients with E. faecalis BSIs.